2001
DOI: 10.1002/14651858.cd003015
|View full text |Cite
|
Sign up to set email alerts
|

Family and parenting interventions in children and adolescents with conduct disorder and delinquency aged 10-17

Abstract: Family and parenting interventions in children and adolescents with conduct disorder and delinquency aged 10-17 (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
89
0
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(98 citation statements)
references
References 30 publications
4
89
0
5
Order By: Relevance
“…• "examine effectiveness" (Curtis, Ronan, & Borduin, 2004) or "determine effects" (Woolfenden, Williams, & Peat, 2003); or…”
Section: Purpose and Hypotheses Regarding Mstmentioning
confidence: 99%
See 1 more Smart Citation
“…• "examine effectiveness" (Curtis, Ronan, & Borduin, 2004) or "determine effects" (Woolfenden, Williams, & Peat, 2003); or…”
Section: Purpose and Hypotheses Regarding Mstmentioning
confidence: 99%
“…Only 4 reviews assessed attrition in primary outcome studies (Brosnan & Carr, 2000;Cormack & Carr, 2000;Farrington & Welsh, 2003;Woolfenden et al, 2003), but all 4 underestimated attrition (Littell, 2005(Littell, , 2006. This is likely due to the practice (articulated by Woolfenden and colleagues) of selecting the most recent report when there were multiple reports per study, instead of tracking attrition over time through different reports.…”
Section: Standards Of Evidencementioning
confidence: 99%
“…Efetividade da colaboração de parentes e familiares na redução no tempo de internação de jovens de 10 a 17 anos em instituições para delinqüentes. (Woolfenden et al 2003). 37 Conclusão: a colaboração de pais e familiares contribui para a redução do tempo de permanência na instituição (não é mencionada a natureza da contribuição dos familiares).…”
Section: Paradigma Da Medicina Baseada Em Evidências E O Fundamentaliunclassified
“…(Woolfenden et al 2003). 37 Conclusão: a colaboração de pais e familiares contribui para a redução do tempo de permanência na instituição (não é mencionada a natureza da contribuição dos familiares).…”
Section: Paradigma Da Medicina Baseada Em Evidências E O Fundamentaliunclassified
“…That is, bullies were more likely to be aggressive, less cooperative, and socially impaired, and they typically had few friends (Conduct Problems Prevention Research Group, 1999;Prinz & Connell, 1997;Webster-Stratton, 1990). Researchers found that this characteristic, like other forms of aggression, was stable over time (Dumas, 1989;Kazdin, 1987;Lytton, 1990;Woolfenden, Williams, & Peat, 2001). In one scenario, researchers hypothesized that as these children age, their behavior puts them at greater odds with their families and peers, thereby leading to increases in aggressive tendencies (Patterson, Dishion, & Bank, 1984).…”
mentioning
confidence: 99%